Programma: 6 april Trumans Water; 7 april Amsterdam hard; 8 april Kanda Bongo Man; 9 april Morphine; 12 april Mutabaurka
Programma: 6 april Trumans Water; 7 april Amsterdam hard; 8 april Kanda Bongo Man; 9 april Morphine; 12 april Mutabaurka.